PENGARUH METODE PROBLEM SOLVING DAN PROBLEM POSING TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA DIMODERASI MINAT BELAJAR PADA MATA PELAJARAN EKONOMI (Studi Kuasi Eksperimen di Kelas XI IPS SMA Negeri 1 Ciwidey Materi Pajak) - Citra Anggreini, - (2020)
This study aims to determine the effect of problem solving and problem posing methods in improving students' problem solving abilities, the effect of interest in learning on problem solving abilities and how they interact with learning methods and interest in learning. The study was conducted in class XI IPS SMAN 1 Ciwidey. This research is a quasi experiment with 2x2 factorial design. Analysis of the data used in the form of Two Way ANOVA SPSS 23. The findings of this study indicate that: 1)There is an effect of problem solving and problem posing learning methods on students' problem solving abilities. In this study it was found that the problem solving method was superior in improving students' problem solving abilities, 2) interest in learning affects students' problem solving abilities, 3) there areinteraction of learning methods problem solving and problem posing on students' problem solving abilities. The conclusion of this research is to assist teachers in choosing learning methods that are appropriate to the material in the learning process in order to improve students' problem solving abilities.